Crushing method selection for non-centrifugal sugar production by FAHP–ELECTRE I. (3rd February 2020) - Srinivas, M; Sravya, B; Raj, S Prudhvi; Reddy, K S
Abstract: The non-centrifugal sugar (NCS) industry is one of the oldest small-scale cottage industry in India, whose technological features are not changed for several decades due to which the production and consumption of NCS has reduced significantly. One way to attend this problem is to select the best and sustainable methods among the existing technologies at various stages in the production process. In the production of NCS, juice extraction is the primary and essential process. The present work gives an insight to a logical procedure for selecting a suitable and sustainable juice extraction method for improving the NCS production using multi-criteria evaluation (MCE) technique. The selection process is based on 11 evaluation criteria covering various sustainable factors viz. technological, economic and environmental factors. Fuzzy analytical hierarchical process (FAHP) integrated with elimination et choix traduisant la realité method is the MCE technique considered for selecting the most appropriate crushing method among five alternatives. The results indicated that the power-operated single horizontal crusher is the most suitable and sustainable crushing method for improving the production rate of NCS. The same technique can be used for the other process unit of the NCS production to improve the productivity and sustainability of NCS.